Nematódeos de quelônios terrestres e dulcícolas da Região Neotropical, com ênfase no Cágado-de-barbicha - Phrynops geoffroanus (Schweigger, 1812) (Testudines: Chelidae) no semiárido brasileiro - Brito, Paulo Henrique Izidro de (2021)
Parasites are considered essential elements in aquatic ecosystems, participating in the energy flow and acting as population controllers acting as ecosystem engineers. The phylum Nematoda has a great taxonomic diversity, with parasitic and free-living representatives, having enormous economic, ecological and zoonotic importance. The neotropical region is considered to be rich in reptile species and there are eight families of terrestrial and freshwater turtles. Phrynops geoffroanus is a medium-sized tortoise and has a high potential as intermediate hosts for numerous parasitic diseases, due to its diet that includes a great diversity of prey. The main objectives of this study were to survey the literature on nematode species of terrestrial and freshwater turtles in the Neotropical Region; check if their bioregions, as well as nematode species have similarity; evaluate the composition of its β diversity, as well as verifying the most registered nematode families and genera; and register the parasitic fauna of P. geoffroanus in the Sertão da Paraíba, northeastern Brazil, verifying whether there is a correlation between P. geoffroanus host characteristics and the abundance and richness of collected helminths. The research was carried out in anthropic rivers in the cities of Conceição and Patos, in the interior of Paraíba, Brazil. Two populations of P. geoffroanus were studied in November and December 2019 and December 2020, totaling 17 specimens captured. The nematode list recorded 10 superfamilies, 17 families, 38 genera and 66. Most nematode species have similarity for a bioregion, forming seven groups; the Chaco Domain had the highest number of records, while the Brazilian Boreal Domain recorded the highest number of species and the Pacific Domain more genera and families of nematodes. The β - diversity was more explained by the rotation of species (turnover), showing that the nematode community is heterogeneous in the domains of the Neotropical Region. The Gnathostomatidae family had the highest record, followed by Camallanidae and Atractidae, being the families that most infect freshwater turtle species. The families Atractidae, Pharyngodonidae and Strongylidae were the ones that most infected terrestrial species. Among the 38 genera of nematodes, Serpinema, Spiroxys and Atractis were the most recorded; being Serpinema, Spiroxys and Falcaustra (in freshwater turtles) and Atracti and Labiduris (in terrestrial turtles). Of the 60 species of nematodes, 81.66% infect the intestines and 38.33% the stomach. The Testudinidae family had the highest number of registered nematode species, followed by Kinosternidae and Podocnemididae. The Testudinidae, Geoemydidae and Chelidae families had more nematode genera. In total, 38 species and 16 genera of turtles were recorded, with the species Chelonoidis denticulatus being the most parasitized host. Considering the freshwater turtles, the species Podocnemis expansa and Podocnemis unifilis were the most parasitized species. Regarding the host P. geoffroanus, two new occurrences of nematodes of the genera Camallanus and Spiroxys were recorded, the first being Camallanus sp. showing higher prevalence (100%) and abundance (n=383) and the second Spiroxys contortus (prevalence: 64.7%; n=49), the first record of the parasite for the host.